Análisis de la deserción estudiantil en los programa de pregrado de la universidad EAFIT (2010)
College desertion is defined as the disruption of higher education undertaken by a student. To identify its causing factors is a subject of great interest for Institutions of Higher Education, because it diminishes the potential to achieve their main purpose: to educate professionals. Therefore, this research approaches college desertion conceptually and methodologically, in order to analyze this phenomenon at EAFIT University. Our sample corresponds to cohorts 2001-1, 2002-1 and 2003-1, belonging to 14 undergraduate programs. Initially the drop-out population was studied through a descriptive exploration of some key indicators and several individual, socio-economic, academic and institutional characteristics. These were followed by two econometric modelings (transversal and longitudinal). Finally a qualitative analysis was made by applying a semi-structured interview to selected students who were classified as deserters. Results highlight a significant early desertion, associated mainly to academic variables and a lack of students’ assertiveness in their choice of undergraduate programs.